Portugal in world war II: The Japanese invasion of Timor - Rocha, J. S. (Boletim da comissão portuguesa de história militar, 2016)
The foreign policy put into practice during the Second World War by the Portuguese authorities demanded a skilled and accurate, but also risky, political and diplomatic action. In general terms, and similar to the situation experienced by the time of World War I, the international positioning of Portugal turned out to be “corseted” by certain conditions of geopolitical order: in European terms, the maintenance of the peninsular duality and the strategic value of the Portuguese Atlantic archipelagos; in colonial terms, the maintenance of its overseas empire.